2021
DOI: 10.4088/jcp.20m13850
|View full text |Cite
|
Sign up to set email alerts
|

Persistence With and Adherence to Paliperidone Palmitate Once-Monthly Injection for Schizophrenia Treatment in China and Japan

Abstract: Objective: To describe persistence with and adherence to paliperidone palmitate once-monthly injection (PP1M) compared to oral second-generation antipsychotics (SGAs) in patients with schizophrenia in real-world settings in China and Japan. Methods: Patients with a schizophrenia diagnosis (ICD-10: F20.x) who

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Despite the aforementioned limitations, data from naturalistic studies (cohort and mirror studies), with PDC as a measure of compliance, consistently describe significantly better adherence patterns in subjects treated with PP compared to OA. Favourable adherence outcomes related to PP have been highlighted in all the studies selected, with similar results both in Asian 34 and US populations. [28][29][30][31][32][33][35][36][37] PP showed higher adherence rates when compared to first-generation 32 and second-generation antipsychotics.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…Despite the aforementioned limitations, data from naturalistic studies (cohort and mirror studies), with PDC as a measure of compliance, consistently describe significantly better adherence patterns in subjects treated with PP compared to OA. Favourable adherence outcomes related to PP have been highlighted in all the studies selected, with similar results both in Asian 34 and US populations. [28][29][30][31][32][33][35][36][37] PP showed higher adherence rates when compared to first-generation 32 and second-generation antipsychotics.…”
Section: Discussionsupporting
confidence: 62%
“…Figure 1 reports a flowchart of all papers evaluated and included in this review. Ten studies were selected: nine retrospective cohort studies [28][29][30][31][32][33][34][35][36] and one mirror study. 37 Among these papers, two studies showed data on adherence patterns only 29,34 and eight studies presented data on adherence levels and other clinical outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations